Ven. Maha Ghosananda’s Contributions to Social Well-Being in Cambodia - Sarun, Ven. Pov (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง; Vol 2 No 2 (2019): ปีที่ 2 ฉบับที่ 2 ประจำเดือนกรกฎาคม - ธันวาคม 2562, 2019)
Cambodia is a Theravada country, which estimates to be 95 percent of its population are the follower of the Buddha; and where the monks hold an important place in the society at large. Buddhism is a part of the development in the social order, and it’s strongly played as social well-being in Cambodia. However, presently, social well-being is very important to the Cambodian Society and its people.  But unfortunately, from April 17, 1975 to January 1979, social well-being in Cambodia was entirely destroyed by the Khmer Rouge.  Due to the fact that the Khmer Rouge starved people to death and isolated the country from other countries, Cambodia and its population were suffering beyond one’s imagination; millions of people died from this civil war.  Many monasteries were destroyed, and monks were killed and forced to lay lives.  In addition, both public and private schoolings were impasses. After the Khmer Rouge Regime, Buddhism was re-established, and slowly began to increase with the re-ordination of Buddhist Monks who ran away from monasteries during the purges.  They came back to monasteries re-establish and re-build monasteries with the supporting of lay Buddhist. Buddhism in Cambodia has deeply flourished after the Khmer Rouge era through the hard work of the Buddhist monks, especially Ven. Maha Ghosananda.  Buddhism in Cambodia is divided into two sects: Mahānikaya and Dhammayutanikaya. Cambodian Buddhism has been growing  and developing in the country under the leadership of Buddhist monks and lay Buddhists.